Probiotics Delay the Decrease of Kidney Function in Patients with Chronic Kidney Disease - Aslul Khitan; Agung Susanto; Lusi Oka Wardhani (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Chronic kidney disease (CKD) is defined as kidney impairment or reduced estimated glomerular filtration rate (eGFR). The prevalence grows over time. A progressive decrease in kidney function eventually necessitates renal replacement therapy (dialysis or transplantation). Appropriate treatment determines the clinical outcome. One of them is the dietary approach. This review aims to gather evidence of the potential of probiotics to delay CKD damage progression. This scoping review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist. The review gathers publications from four databases and synthesizes them as evidence. Were 357 publications found, three of which matched the inclusion criteria and were evaluated. The article's synthesis results reveal that probiotics suppress intestinal dysbiosis. These beneficial complicated processes make significant contributions. Thereby, the worsening of renal disease is prevented. Based on the findings, it was concluded that the probiotic positively affected the clinical outcomes of chronic kidney disease.